Observations on nudibranch behaviour patterns under laboratory conditions - Abdallah, Ali Alqudah; Saad, Shahbudin; Darnis, Deny Susanti; Nordin, Noor Faizul Hadry; Khodzori, Mohd Fikri Akmal; Yusof, Muhammaad Hamizan; Rani, Mohd Husaini (Penerbit Universiti Teknologi Malaysia, 2016)
Phyllidiid Nudibranchs Phyllidia varicosa and Phyllidiella pustulosa were observed under laboratory conditions and abnormal behaviours were recorded. This study described the manoeuvering, mating behaviour, egg laying and abnormal activities. Some abnormal behaviours were recorded while retaining the sample in the aquarium such as emitting noxious chemicals, lifting up the mantle edge to expose the gills and crawling towards the water surface and lie there. Maneuvering behaviour was distinguished when two individuals were interacting with each other before the mating. Mating behaviour started by extending and joining the reproductive organs followed by gamete exchange for several minutes. During the mating behaviour, there was a limited movement like contracting of the body and hiding the rhinophores into the rhino-tube. Egg deposition was observed in the aquarium as natural behavior after mating and as a stress response after placing the sample in the captivity.